Tension–bend–shear capacity of bolted-flange connection for square steel tube column. (15th December 2019) - Liu, Xue-Chun; Cui, Fu-Yuan; Jiang, Zi-Qin; Wang, Xiao-Qing; Xu, Lu; Shang, Zi-Xuan; Cui, Xiao-Xiong
Graphical abstract: Highlights: Performance of bolted-flange connections under tension, moment and shearing. Static tension, moment and shearing tests and FEA on bolted-flange connections. Effect of flange thickness, bolt edge distance, flange edge width and bolt hole size. Stiffness and strength of connections, bolt tension and contact force were obtained. Yield bearing capacity obtained from proposed formulas agreed well with test and FEA. Abstract: In this study, the square steel tube column is connected by bolted flange instead of traditional welding. For multi-rise structure, tension, bending moment, and shear force may act on the connection under vertical and horizontal loads. To investigate the mechanical behavior of flange connections, full-scale model tests and finite element analyses of 10 bolted-flange joints were carried out. The mechanical properties of the specimens and the influence of the flange thickness, flange size, and bolt hole diameter under a tension–bend–shear combination were obtained. The size of the bolt hole and flange has little effect on the load-carrying capacity of the connection. With the increase of the thickness of flange, the flexural rigidity and load-carrying capacity of the connection increase obviously, and the yield mechanism of the specimen changes from flange yield to bolt yield. The influence of the axial tension ratio on the bolt tension was investigated by the experiment-verified finite element models. The axial tension ratio is the value that the axial force of column divided by the cross-sectional area and the material design strength of the column. Increasing the axial tension ratio may increase the bolt tension, which has a harmful effect on the bolts at the tension side of the flange. Using yield line theory, formulas for calculating the static load-bearing capacity resisting the bending moment, shear and tension were deduced and verified by comparing with the result of experiment and finite element analysis.